2015
DOI: 10.1080/10402004.2014.998358
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Wear and Friction Characteristics of Epoxy Resin by Multiwalled Carbon Nanotube and Boron Nitride Nanoparticles

Abstract: Epoxy resin is widely used in engineering applications. However their low thermal stability limits their usage at high sliding velocities and loads. The mechanical properties and thermal stability of a machine element subjected to friction and wear is very important. In this study, friction and tribology behaviors of MWCNT and BN modified epoxy resin have been investigated. Epoxy resin modified by three different nano particle configurations as 0.3% MWCNT, 0.5% BN and 0.5%MWCT/0.3%BN. The tribology characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 23 publications
1
25
0
1
Order By: Relevance
“…Further, the authors stated that the improvement in load‐carrying and EP ability of lube oil was enhanced due to the dispersion of hBN nanoparticles. The tribological characteristics of epoxy resin were studied by Hayrettin et al 30 using MWCNT and hBN as nanoparticles additive in epoxy resin by using a ball‐on‐disc test. The results revealed that modified epoxy resin has shown improved wear resistance and friction reduction behavior at higher working temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the authors stated that the improvement in load‐carrying and EP ability of lube oil was enhanced due to the dispersion of hBN nanoparticles. The tribological characteristics of epoxy resin were studied by Hayrettin et al 30 using MWCNT and hBN as nanoparticles additive in epoxy resin by using a ball‐on‐disc test. The results revealed that modified epoxy resin has shown improved wear resistance and friction reduction behavior at higher working temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the tribological testing results shows that the friction coefficient with CNTs is far less than that without CNTs. We conclude that during dry sliding tests, adding CNTs as a solid lubricant to the PRCL system can greatly decrease friction [26] because CNTs cover the contact surfaces and have sp2 bonding that generates a lower shear force and helps to reduce friction [15,27]. Moreover, a decrease in the friction coefficient can reduce the heat generated during sliding.…”
Section: Surface Analysismentioning
confidence: 86%
“…For example, Yan et al [14] investigated the friction and wear properties of pure epoxy resin and aligned carbon nanotube-reinforced epoxy resin composites under water lubricated conditions and found that the latter showed a lower friction coefficient and higher wear rates than pure epoxy resin. Düzcükoğlu et al [15] 148 Friction 5(2): 147-154 (2017) | https://mc03.manuscriptcentral.com/friction and Cui et al [16] investigated the tribological behavior of multiwall carbon nanotube (MWCNT)modified epoxy resin under dry sliding conditions and concluded that nanoparticle modification resulted in enhanced wear resistance and reduced friction coefficient and working temperature under dry conditions. LaBarre et al [17] evaluated the influence of MWCNTs on the impact performance and contributing constituent properties of Kevlar.…”
Section: Introductionmentioning
confidence: 99%
“…investigated the tribological behaviour of alumina‐filled glass‐epoxy composites; it was found that these composites showed semiductile erosion behaviour, with peak erosion rate occurring at 60° impingement angle. Düzcükoğlu et al . investigated the friction and tribology behaviour of multiwall carbon nanotube and boron nitride modified epoxy resin; the results showed that the nanoparticle modification was a result of enhancement in wear resistance and reduction in friction coefficient and working temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Biswas et al [9] investigated the tribological behaviour of alumina-filled glass-epoxy composites; it was found that these composites showed semiductile erosion behaviour, with peak erosion rate occurring at 60°impingement angle. Düzcükoğlu et al [10] investigated the friction and tribology behaviour of multiwall carbon nanotube and boron nitride modified epoxy resin; the results showed that the nanoparticle modification was a result of enhancement in wear resistance and reduction in friction coefficient and working temperature. Graphene (G) is a monolayer carbon atom material with twodimensional structure and high specific surface area, high level of stiffness, strength and thermal conductivity properties, and it is often filled into organic matrix as an enhancement phase.…”
Section: Introductionmentioning
confidence: 99%